NLRP3, NLRP12, and IFI16 Inflammasomes Induction and Caspase-1 Activation Triggered by Virulent HSV-1 Strains Are Associated With Severe Corneal Inflammatory Herpetic Disease - Coulon, Pierre-Gregoire; Dhanushkodi, Nisha; Prakash, Swayam; Srivastava, Ruchi; Roy, Soumyabrata; Alomari, Nuha I.; Nguyen, Angela M.; Warsi, Wasay R.; Ye, Caitlin; Carlos-Cruz, Edgar A.; Mai, Uyen T.; Cruel, Audrey C.; et al. (Frontiers in Immunology, 2019)
The crosstalk between the host’s inflammasome system and the invading virulent/less-virulent viruses determines the outcome of the ensuing inflammatory response. An appropriate activation of inflammasomes triggers antiviral inflammatory responses that clear the virus and heal the inflamed tissue. However, an aberrant activation of inflammasomes can result in a harmful and overwhelming inflammation that could damage the infected inflamed tissue. The underlying host’s immune mechanisms and the viral virulent factors that impact severe clinical inflammatory disease remain to be fully elucidated. In this study, we used herpes simplex virus type 1 (HSV-1), the causative agent of corneal inflammatory herpetic disease, as a model pathogen to determine: (i) Whether and how the virulence of a virus affects the type and the activation level of the inflammasomes; and (ii) How triggering specific inflammasomes translates into protective or damaging inflammatory response. We showed that, in contrast to the less-virulent HSV-1 strains (RE, F, KOS and KOS63), corneal infection of B6 mice with the virulent HSV-1 strains (McKrae, 17 or KOS79): (i) Induced simultaneous high expression levels of the NLRP3, NLRP12 and IFI16 inflammasomes; (ii) Increased production of the biologically active Caspase-1 and pro-inflammatory cytokines IL-1 and IL-18; (iii) Heightened recruitment into the inflamed cornea of CD45highLy6C+Ly6G−F4/80+CD11b+CD11c− inflammatory monocytes and CD45highCD11b+F4/80−Ly6GhiLy6Cmed neutrophils; and (iv) This intensified inflammatory response was associated with a severe corneal herpetic disease, irrespective of the level of virus replication in the cornea. Similarly, in vitro infection of human corneal epithelial cells and THP‑1 cells with the virulent HSV-1 strains triggered a synchronized early expression of NLRP3, NLRP12 and IFI16, two hours post-infection, associated with formation of single and dense specks of the adapter molecule ASC in HSV(+) cells, but not in the neighboring bystander HSV(-) cells. This was associated with increased cleavages of Caspase-1, IL-1 , and IL-18. These findings suggest a previously unappreciated role of viral virulence in a synchronized early induction of the NLRP3, NLRP12 and IFI16 inflammasomes that lead to a damaging inflammatory response. A potential role of common virus virulent factors that stimulate this harmful inflammatory corneal disease is currently under investigation.